P374 Fungal coinfection in patients with SARS-CoV-2: Atertiary care hospital study. (20th September 2022) - Saini, Vikas; Rai, Gargi; Singh, Praveen; Das, Shukla; Singh, Narendra Pal
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM:   Background: There is a high risk of developing fungal co-infections in patients infected with SARS-CoV-2, few studies have been conducted on the incidence and risk of these secondary infections. The incidence of Candida infection due to different Candida species is increasing in COVID patients. Methods: This retrospective study comprised a total of 23 patients with upper respiratory infection investigated in the Department of Microbiology of University College of Medical Sciences (UCMS) and Guru Teg Bahadur Hospital (GTBH), Delhi from April 2021 to June 2021. Identification was done using DNA sequencing. Results: Of the 23 cases, identification by DNA sequencing, C. albicans was present in 34.78%, C. tropicalis in 30.43%, Pichia kudriavzevii in 26.08%, C. parapsilosis in 4.3%%, and C. auris in 4.3%. Conclusion: C. albicans is the leading pathogen in our patients, along with the rise in the incidence of P. kudriavzevii which is usually an environmental contaminant. Regular surveillance and infection control practices are future ventures to reduce the burden of infection.